Self-Protective Motivation and Compliance with COVID-19 Health Protocols among Undergraduate Nursing Students - Malini, Hema; Krisdianto, Boby Febri; Lenggogeni, Devia Putri; Armes, Al Hanifah (Fakultas Ilmu-ilmu Kesehatan, 2024)
Students who gather and do not pay attention to health protocols can be evidence of their low compliance with implementing health protocols. University students, particularly those who come from health faculties, are considered change agents in implementing health protocols. Thus, it is necessary to examine their motivation and attitude toward implementing health protocols. This study aimed to determine the relationship between self-protective motivation and compliance with the nursing students' health protocol. The study was carried out with 253 undergraduate nursing students selected through cluster sampling with a cross-sectional design. The results showed that most of the students complied with the health protocols; some already had motivations related to self-protective motivation against COVID-19 and some already had a positive attitude towards the health protocol. There is a significant relationship between self-protection motivation and compliance with the nursing student health protocol (p-value = 0.000). However, nursing students must increase self-protective motivation and positive attitudes by increasing their understanding and confidence in the dangers of COVID-19 to encourage their obedience to health protocols. More studies need to be conducted to investigate the causes of student non-compliance in implementing health protocols, especially in the campus environment.